2023
DOI: 10.3390/microorganisms11051122
|View full text |Cite
|
Sign up to set email alerts
|

Gastroparesis: The Complex Interplay with Microbiota and the Role of Exogenous Infections in the Pathogenesis of the Disease

Abstract: Gastroparesis (GP) is a disorder of gastric functions that is defined by objective delayed gastric emptying in the absence of mechanical obstruction. This disease is characterized by symptoms such as nausea, post-prandial fullness, and early satiety. GP significantly impacts patients’ quality of life and contributes to substantial healthcare expenses for families and society. However, the epidemiological burden of GP is difficult to evaluate, mainly due its significant overlap with functional dyspepsia (FD). G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 130 publications
(141 reference statements)
0
4
0
Order By: Relevance
“…The role of H. pylori in EAC risk remains unclear. A meta-analysis of 28 studies found an inverse relationship, suggesting that H. pylori infection may confer protection against EAC [130] . However, other studies have found no clear association or have produced inconclusive results [131] .…”
Section: Malignant Esophageal Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…The role of H. pylori in EAC risk remains unclear. A meta-analysis of 28 studies found an inverse relationship, suggesting that H. pylori infection may confer protection against EAC [130] . However, other studies have found no clear association or have produced inconclusive results [131] .…”
Section: Malignant Esophageal Diseasementioning
confidence: 99%
“…DGE primarily arises from anatomical and physiological post-surgical abnormalities, such as peristalsis dysfunction resulting from complete vagotomy, gastric conduit torsion [129] , and pyloric spasm. However, there is evidence demonstrating that the composition of the microbiota can influence gastric emptying [130] . Furthermore, it is widely recognized that changes in intestinal bacteria can significantly affect gastrointestinal motility [131] .…”
Section: Post-surgical Complicationsmentioning
confidence: 99%
“…An additional avenue for exploration is based on the specificity of effects of different strains of B. subtilis on gut microbiome. Microbiota modifications seem to be a major player in many GI tracts and other organ system disorders, including gastroparesis and endometriosis in conjunction with IBS, as highlighted in recent reviews [63,64]. The effects of B. subtilis as a transient probiotic but not a permanent GI resident is largely unexplored in the context of these diseases, which opens a wide area for future clinical research.…”
Section: Future Perspectives For Probiotic Bacillus Subtilis In Human...mentioning
confidence: 99%
“…The involvement of the human intestinal microbiome has been firmly established in the pathophysiology of various gastrointestinal organic diseases, including colorectal polyps and cancer [ 12 , 13 ], inflammatory bowel diseases [ 14 ], and eosinophilic esophagitis [ 15 ]. Furthermore, it has been implicated in gastroparesis [ 16 , 17 ] and the occurrence of post-surgical complications [ 18 , 19 ] that necessitate endoscopic treatment [ 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%